Serum lipid metabolites predict the efficacy of intravenous immune globulin therapy in patients with pediatric dilated cardiomyopathy - Zhiyuan Wang; Yanyan Xiao; Haichu Wen; Yifei Yang; Meng Yuan; Meng Jiao; Yan Gu; Mei Jin; Jie Du (Scientific Reports)
Abstract The response of pediatric dilated cardiomyopathy (PDCM) patients to intravenous immune globulin (IVIG) varies from cardiac functional recovery to heart transplantation and even death. IVIG therapy can significantly improve the left ventricular ejection fraction (LVEF) in some PDCM patients, but indicators for evaluating the response to IVIG therapy are lacking. Lipid metabolic disturbance is associated with changes in cardiac function, but no studies have examined the associations between lipidomics markers and the efficacy of IVIG. Discovery analyses were based on 322 targeted lipids in a retrospective cohort study. T tests, orthogonal‒orthogonal projections to latent structures discriminant analysis (OPLS-DA) and random forest (RF) analysis were used to screen the candidate lipids. Associations of the candidate lipids were examined via Cox proportional hazards regression models. We subsequently developed a score for the candidate lipid metabolites, which was then used to classify children into two groups (0–3 and 4), and the survival curves of the two groups were drawn. There were 31 patients in the discovery set and 24 patients in the validation set. Adverse events which were defined as death, heart transplant, and rehospitalization for HF were observed in 23 patients (41.8%). After adjusting for age, LVEF, and the LV end-diastolic diameter z score, CE-16:1, PE36:4p, PE40:6p, and PE40:6p (22:6) were significantly associated with the occurrence of adverse events in the discovery set. The results were also consistent in the validation set, and the hazard ratios (HRs) were 2.638 (95% CI 1.042–6.683; p = 0.041), 0.549 (95% CI 0.340–0.886; p = 0.014), 0.271 (95% CI 0.109–0.672; p = 0.005), and 0.299 (95% CI 0.121–0.741; p = 0.009), respectively. We developed a score for these four lipid metabolites. When the score reached 4, adverse events were more likely to be observed in both sets. Serum lipid metabolites can be used to predict the efficacy of IVIG in children with DCM.